2011
DOI: 10.1007/s11627-011-9398-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flask sealing and growth regulators on in vitro propagation of neem (Azadirachta indica A. Juss.)

Abstract: In vitro propagation of neem (Azadirachta indica A. Juss.) may offer an efficient alternative to seed propagation of this species. For optimization of in vitro propagation, different basal salt formulations, growth regulators, and culture container sealants (polytetrafluoroethylene hydrophobic membranes [PTFE]) were evaluated. Nodal segments cultured on Murashige and Skoog (MS) medium showed the highest shoot formation per explant (1.67). Explants cultured in flasks containing MS medium with 0.5 mg L −1 benzyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
1
20
0
8
Order By: Relevance
“…O mesmo foi observado por Rodrigues et al (2011), os quais encontraram que nos frascos com membranas porosas houve trocas gasosas, evitando, assim, o acúmulo do gás etileno dentro dos frascos, sendo observado o oposto nos frascos com tampa rígida sem orifício. No entanto, Zobayed et al (2000) observaram que o uso das membranas porosas não é capaz de remover completamente a concentração do gás etileno produzido pelas plantas in vitro.…”
Section: Influência Do Tipo De Vedação Em Tubos De Ensaiounclassified
See 2 more Smart Citations
“…O mesmo foi observado por Rodrigues et al (2011), os quais encontraram que nos frascos com membranas porosas houve trocas gasosas, evitando, assim, o acúmulo do gás etileno dentro dos frascos, sendo observado o oposto nos frascos com tampa rígida sem orifício. No entanto, Zobayed et al (2000) observaram que o uso das membranas porosas não é capaz de remover completamente a concentração do gás etileno produzido pelas plantas in vitro.…”
Section: Influência Do Tipo De Vedação Em Tubos De Ensaiounclassified
“…Diferente do que foi observado por Rodrigues et al (2011), que relataram que o uso de tampas com membranas porosas influenciaram positivamente o estabelecimento das culturas, além de aumentarem a qualidade e quantidade de brotos e diminuírem a ocorrência de clorose e senescência nas folhas de Azadirachta indica A. Juss. Foi o que observaram Ribeiro et al (2009) em Solanum melongena L., em que as plantas mantidas no mesmo tipo de vedação (tampas com membranas porosas) apresentaram-se maiores e mais vigorosas, além de apresentarem folhas e raízes maiores e mais desenvolvidas.…”
Section: Influência Do Tipo De Vedação Em Tubos De Ensaiounclassified
See 1 more Smart Citation
“…RODRIGUES et al (2011) evaluating the effect of gas exchange on the in vitro propagation of neem (Azadirachta indica), suggested that the use of membranes that allow higher gas exchange can improve shoot quality, reducing the occurrence of chlorosis and leaf senescence. Similarly, we observed that plantlets of C. annuum cultured under higher gas exchange conditions showed less occurrence of leaf abscission, senescence, hyperhydricity, and chlorosis.…”
Section: Resultsmentioning
confidence: 99%
“…MilliSeal ® membranes have been successfully used to improve gas exchange in the culture flask in the propagation of many species, including Pfaffia glomerata (IAREMA et al, 2012;SALDANHA et al, 2013SALDANHA et al, , 2014CORRÊA et al, 2015), Azadirachta indica (RODRIGUES et al, 2011), Alha gigraecorum (ZOBAYED et al, 2006), and Eucalyptus tereticornis (SHAVALLI KHAN et al, 2002).…”
Section: Introductionmentioning
confidence: 99%